Pengembangan UMKM Melalui Peningkatan Pengetahuan Masyarakat Terhadap Proses Produksi dan Pemasaran - Supriatna, Asep Deddy; Naufal, Shofwan Dzaki; Bintang, Muhammad; Pertiwi, Asri Indah; Nuraeni, Siska; Amelia, Shalma; Herlina, Lina; Arianto, Mohamad Jefry; Mutaqien, Rizky; Nasrulloh, Anas; Ajijah, Ayu Nur Isti; Jembar, Tegar Hanafi; Abdussalam, Iqbal; Aliansyah, Difa Eka; Fahreza, Reynaldi; Rohimat, M. Galuh Fajar; Rustandy, Sandy; Alamsyah, Hadi; Lestari, Ayu; Diningrat, Galant Ababil Haqti (Institut Teknologi Garut, 2022)
The majority of MSME actors in Sukamenak Village have mostly elementary and junior high school education so they can be categorized as having low education. This has an impact on increasing production and marketing capacity. The main problem in marketing knowledge starts with MSME players, especially Papandak coffee and palm sugar, who only market their products without advertising support, both traditionally and digitally. The Digital Literacy Seminar training program regarding increasing MSME marketing aims to increase the capacity of MSME actors in marketing products and improve the quality of marketing knowledge. The methodology used is the ICT Volunteer Integration methodology, where the implementation method uses the offline method. The results achieved were by increasing the knowledge of MSME actors in product marketing so as to help increase the marketing capacity of MSMEs for Papandak coffee and palm sugar.